Carbon Material Optimized Biocathode for Improving Microbial Fuel Cell Performance - Tursun, Hairti; Liu, Rui; Li, Jing; Abro, Rashid; Wang, Xiaohui; Gao, Yanmei; Li, Yuan (Frontiers in Microbiology, 2016)
To improve the performance of microbial fuel cells (MFCs), the biocathode electrode material of double-chamber was optimized. Alongside the basic carbon fiber brush, three carbon materials namely graphite granules, activated carbon granules and activated carbon powder, were added to the cathode-chambers to improve power generation. The result shows that the addition of carbon materials increased the amount of available electroactive microbes on the electrode surface and thus promote oxygen reduction rate, which improved the generation performance of the MFCs. The Output current (external resistance = 1000 Ω) greatly increased after addition of the three carbon materials and maximum power densities in current stable phase increased by 47.4%, 166.1% and 33.5%, respectively. Additionally, coulombic efficiencies of the MFC increased by 16.3%, 64.3% and 20.1%, respectively. These results show that MFC when optimized with activated carbon granules show better power generation, higher chemical oxygen demands (COD) removal rate and coulombic efficiency.